Modelling of air quality and atmospheric deposition in Hungary - Bozó, László; Labancz, Krisztina; Steib, Roland (TÁJÖKOLÓGIAI LAPOK, 2008)
Annual average atmospheric concentrations and depositions of sulfur and nitrogen species, as well as trace metals in Hungary and its surrounding regions were estimated by model computations. Spatial and temporal variations of the distributions are presented in the paper. The temporal variation of atmospheric sulfur budget was calculated based on a simple atmospheric box model. In the case of atmospheric lead, the cumulative atmospheric depositions were also estimated for a sixty years long period until 2015 using historical emission factors for the past decades as well as emission scenarios for the future. It was found that Hungary belongs to the moderately polluted regions in Europe. A model hierarachy was developed in order to perform multi-scale modelling studies on the air pollution processes at different spatial and temporal scales in Hungary. A set of environmental indicators was defined to characterize the actual state of the atmospheric environment.